OPTIMASI BIAYA DISTRIBUSI TAHU DAN TEMPE MENGGUNAKAN METODE NORTH WEST CORNER (NWC) PADA PABRIK APO GUDANG JAYAPURA - Daniel Bienfield Manahan Siahaan; Jered Imanuel Wanda, Helson Matuan, Yusuf Patey, Esau Dude, Heru Sutejo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
Distribution is one of the important aspects in the supply chain that plays a major role in the operational cost efficiency of a company. This study aims to optimise the distribution costs of tofu and tempeh from the Apo Gudang Factory to several destination markets in Jayapura using the North West Corner (NWC) method. This method was selected due to its simplicity in providing an initial solution to distribution problems involving the allocation of shipments from two warehouses to four market locations, considering supply capacity, demand, and transportation costs per unit. The study was conducted using a descriptive quantitative approach with primary data obtained directly from the factory in May 2025. The research stages included field observations, transportation table compilation, application of the NWC method, distribution cost calculations, and analysis of results. The results of the study indicate that daily distribution costs can be reduced from IDR15,000 to IDR 400,000, resulting in an efficiency of IDR 15,000 per day. Although the solution from the NWC method may not be globally optimal, it can serve as a basis for further improvements using optimisation methods such as MODI or Stepping Stone. Thus, the application of the NWC method in the distribution of tofu and tempeh factories has proven to provide a systematic and efficient initial solution. This study provides a concrete example that a mathematical approach in distribution management can help companies reduce operational costs and improve the effectiveness of logistics strategies